1996
DOI: 10.1016/0304-3959(96)03187-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerance of repeated oral doses of tolperisone hydrochloride in the treatment of painful reflex muscle spasm: results of a prospective placebo-controlled double-blind trial

Abstract: The efficacy and safety of oral tolperisone hydrochloride (Mydocalm) in the treatment of painful reflex muscle spasm was assessed in a prospective, randomized, double-blind, placebo-controlled trial. A total of 138 patients, aged between 20 and 75 years, with painful reflex muscle spasm associated with diseases of the spinal column or proximal joints were enrolled in eight rehabilitation centers. Patients were randomized to receive either 300 mg tolperisone hydrochloride or placebo for a period of 21 days. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
26

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 8 publications
0
41
0
26
Order By: Relevance
“…One high quality trial (N=112) showed that tolperisone is more effective than placebo for short-term (after 21 days) overall improvement, but not for pain relief or reduction of muscle spasm (Pratzel et al 1996).…”
Section: B) Non-benzodiazepines Vs Placebomentioning
confidence: 99%
See 1 more Smart Citation
“…One high quality trial (N=112) showed that tolperisone is more effective than placebo for short-term (after 21 days) overall improvement, but not for pain relief or reduction of muscle spasm (Pratzel et al 1996).…”
Section: B) Non-benzodiazepines Vs Placebomentioning
confidence: 99%
“…All these sideeffects were consistently reported for many of the benzodiazepines and non-benzodiazepines reviewed, with the exception of addiction for non-benzodiazepines. However, two high quality trials showed that neither flurpirtin (Worz et al 1996) nor tolperisone (Pratzel et al 1996) were associated with a higher incidence of adverse events compared with placebo. It is known that tolperisone can have severe allergic side-effects and that flurpirtin can induce reversible reduction of liver function.…”
Section: Safetymentioning
confidence: 99%
“…Three studies were identified [13,153,209]. One high quality trial showed that there is moderate evidence (one trial; 107 people) that flupirtin is more effective than placebo for patients with chronic LBP on short-term pain relief and overall improvement after 7 days, but not on reduction of muscle spasm [209].…”
Section: Muscle Relaxantsmentioning
confidence: 99%
“…One high quality trial showed that there is moderate evidence (one trial; 107 people) that flupirtin is more effective than placebo for patients with chronic LBP on short-term pain relief and overall improvement after 7 days, but not on reduction of muscle spasm [209]. One high quality trial showed that there is moderate evidence (one trial; 112 people) that tolperisone is more effective than placebo for patients with chronic LBP on short-term overall improvement after 21 days, but not on pain relief and reduction of muscle spasm [153].…”
Section: Muscle Relaxantsmentioning
confidence: 99%
“…в 1996 г. [6]. В этом исследовании толперизон гидрохлорид продемонстрировал существенное превосходство перед плацебо в отношении редукции рефлекторного болез-ненного мышечного спазма, обусловленного патологией позвоночника или проксимальных суставов.…”
Section: неврологияunclassified